Serbia and Brics: formalization of relations and possibilities for further cooperation - Proroković, Dušan (Sociološki pregled, 2025)
In October 2024, the formalization of Serbia’s relations with BRICS practically began. Although Serbia is deeply integrated into the structures of the collective West, which is reflected in its domestic policy, the formalization of relations with BRICS has specific weight due to its further foreign policy positioning. Namely, Serbia bases its neutrality not on domestic, but on foreign policy, and in this context, BRICS represents a desirable partner. The aim of the research is to examine the reasons for Serbia’s rapprochement with BRICS, as well as the possibilities of further cooperation. The research is based on the theory of realism (proving the use of the principle of self-help), and the methodological framework is based on the methods of discourse analysis, case study and synthesis.